Synthesis and Antimicrobial Activity Evaluation of Imidazole‐Fused Imidazo[2, 1‐b][1, 3, 4]thiadiazole Analogues. (22nd April 2021) - Yan Guo, Fang; Ji Zheng, Chang; Wang, Meiyuan; Ai, Jiangping; Ying Han, Lan; Yang, Liu; Fang Lu, Ye; Xuan Yang, Yu; Guan Piao, Ming; Piao, Hu‐Ri; Jin, Chun‐Mei; Jin, Cheng Hua
Abstract: Three series of new imidazole‐fused imidazo[2, 1‐ b ][1, 3, 4]thiadiazole analogues (compounds 20 a –g, 21 a –g, and 22 a –g ) have been synthesized, and their antibacterial and antifungal activities have been evaluated. All the target compounds showed strong antifungal activity and high selectivity for the test fungus Candida albicans over Gram‐positive and ‐negative bacteria. N ‐((4‐(2‐Cyclopropyl‐6‐(4‐fluorophenyl)imidazo[2, 1‐ b ][1, 3, 4]thiadiazol‐5‐yl)‐5‐(6‐methyl‐pyridin‐2‐yl)‐1 H ‐imidazol‐2‐yl)methyl)aniline (21 a ) showed the highest activity against C. albicans (MIC50 =0.16 μg/mL), 13 and three times that of the positive control compounds gatifloxacin and fluconazole, respectively. Compounds 21 a and 20 e did not show cytotoxicity against human foreskin fibroblast‐1 cells, and compound 21 a was as safe as the positive control compounds in hemolysis tests. These results strongly suggest that some of the compounds produced in this work have value for development as antifungal agents. Abstract : Treating fungal infection : A series of imidazole fused imidazo[2, 1‐ b ][1, 3, 4]thiadiazoles were synthesized as potent, selective inhibitors of fungal for Candida albicans reduced chronic dermatomucoso candidiasis. The most potent compound, 21 a, showed druglike properties with low cytotoxicity and hemolysis.